2009
DOI: 10.1007/s00468-009-0326-z
|View full text |Cite
|
Sign up to set email alerts
|

Response of Pinus sylvestris L. to recent climatic events in the French Mediterranean region

Abstract: Exceptional climatic events from 2003 to 2005 (scorching heat and drought) affected the whole of the vegetation in the French Mediterranean region and in particular the Scots pine (Pinus sylvestris L.), one of the most important forest tree species in this area. To understand its response to these extreme conditions, we investigated its radial growth, branch length growth, architectural development and reproduction for the period 1995-2005, and linked these variables to climatic parameters. We used four plots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 29 publications
7
65
1
3
Order By: Relevance
“…In contrast, in years when precipitation was abnormally low and temperatures were higher than usual, most trees formed narrow rings. Our findings are in line with recent detailed intra-annual studies of P. sylvestris tree-ring formation Oberhuber and Gruber 2010;Eilmann et al 2011), which confirmed previous conclusions (Antonova et al 1995;Rigling et al 2001; Eilmann et al Thabeet et al 2009) that drought stress hinders cell production in P. sylvestris and thus may have profound effects on tree-ring width. The effect of moisture deficiency on tree-ring width in our study sites was most pronounced during several known drought periods-namely in 1917-1919, 1945-1948 and 1984-1994.…”
Section: Altitude Influence On Climate-growth Relationshipssupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, in years when precipitation was abnormally low and temperatures were higher than usual, most trees formed narrow rings. Our findings are in line with recent detailed intra-annual studies of P. sylvestris tree-ring formation Oberhuber and Gruber 2010;Eilmann et al 2011), which confirmed previous conclusions (Antonova et al 1995;Rigling et al 2001; Eilmann et al Thabeet et al 2009) that drought stress hinders cell production in P. sylvestris and thus may have profound effects on tree-ring width. The effect of moisture deficiency on tree-ring width in our study sites was most pronounced during several known drought periods-namely in 1917-1919, 1945-1948 and 1984-1994.…”
Section: Altitude Influence On Climate-growth Relationshipssupporting
confidence: 93%
“…Water shortage and stress are known to strongly influence cell metabolism and division and thus have an impact on tree-ring formation (Whitmore and Zahner 1967;Antonova et al 1995). In analogy with studies of tree-ring formation in coniferous species at sites with similar ecological conditions, we expect that latewood cell production at our sites starts in July, and cell wall thickening and lignification continues into October (Gindl et al 2001;Camarero et al 1998;Rigling et al 2001;Eilmann et al 2011), but may be terminated earlier due to dry conditions (Thabeet et al 2009;Gruber et al 2010;Eilmann et al 2011). Thus, droughts in July and August may considerably influence the stages of latewood cell production and development.…”
Section: Tree-ring Features and Climate Extremesmentioning
confidence: 84%
“…Recent studies on tree architectural development and primary growth suggested that the long lasting impact of repeated droughts on tree crown development could be one of the causes of these delayed effects [12][13][14].…”
Section: Contextmentioning
confidence: 99%
“…The aims of this work were (1) to detect drivers of current pine and oak occurrence in a mountain region of the southwestern Alps, by fitting species distribution models (SDM) on climate, soil, land use, stand structure, and disturbance-related predictors; (2) to apply the models using future (2080) scenarios, in order to assess if and where vegetation shifts are likely to occur under climate and management changes; and (3) to compare the effects of the Europe-wide drought events of (Thabeet et al 2010 on Scots pine vitality against SDM predictions in 2080, in order to assess the potential role of extreme drought response as an early warning of future vegetation changes.…”
Section: Introductionmentioning
confidence: 99%